IoT-Based Flood Monitoring System with LoRa Communication and Automatic Gate Barrier - Roshamzani, Irdina Nur Nadhirah; Ali, Siti Hajar Aminah (Evolution in Electrical and Electronic Engineering, 2026)
Flooding remains a major natural disaster in Malaysia, causing extensive property damage and threatening human safety, particularly in flood-prone residential areas. Existing flood mitigation systems are often manually operated, costly, or limited in coverage, leading to delayed responses during sudden flood events. This study presents an IoT-based smart flood monitoring system utilising LoRa communication and an automatic gate barrier for real-time flood mitigation. The architecture employs a decentralised design: a detection unit utilising discrete float-switch sensors, a LoRa-integrated transmitter for long-range data propagation, and a receiver node for real-time actuation and Telegram notification. Managed by an ESP32 microcontroller, the system implements a tri-level threshold logic comprising Normal, Warning, and Danger states. At the Warning level, the gate is partially deployed to 45° and a Telegram alert is issued. Meanwhile, at the Danger level, full deployment to 90° is executed. Experimental results indicate stable indoor LoRa communication up to 10 meters with RSSI values ranging from –53 dBm to –67 dBm and SNR up to 10.50 dB. Under outdoor line-of-sight (LOS) conditions, LoRa communication was successfully maintained up to 50 m, with RSSI decreasing to –90 dBm and SNR between 1.50 dB and 5.75 dB. Although signal degradation increased with distance, alert notifications were still received at 50 m, while communication failed beyond 60 m due to the receiver’s sensitivity limits. The findings suggest that this integrated framework offers a scalable and cost-effective solution for autonomous flood management and disaster risk reduction.